Differ we must : how Lincoln succeeded in a divided America - Inskeep, Steve (Penguin Press, 2023)
"From journalist and historian Steve Inskeep, a compelling and nuanced exploration of the political acumen of Abraham Lincoln via sixteen encounters before and during his presidency, bringing to light not only the strategy of a great politician who inherited a country divided, but lessons for our own disorderly present. In 1855, as the United States found itself at odds over the issue of slavery, then lawyer Abraham Lincoln composed a note on the matter to his close friend, the heir to a slaveholding family in the South. Lincoln--who was morally against the institution of slavery--rebuked his friend for his opposing views, he lectured him, he challenged him. But in the end, he wrote: "If for this you and I must differ, differ we must." Throughout his life and political career, Lincoln often agreed to disagree. Democracy demanded it--even an adversary had a vote. The man who went on to become the sixteenth president of the United States has assumed many roles in our historical consciousness, but most notable is that he was, with no apology, a politician. And as Steve Inskeep argues, it was because he was willing to engage in politics--to work with his critics, to compromise with those whom he deeply opposed, and to move only as fast as voters would allow--that he was able to lead a social revolution. In Differ We Must, Inskeep illuminates this master politician's life through sixteen encounters. Some of these meetings are well known, and others more obscure, but all take on new significance when examined in detail. Each interaction was with a person who differed from Lincoln, and in each someone wanted something from the other. While it isn't clear if Lincoln was able to alter his critics' beliefs--many went to war against him--nor if they were able to change his, what is notable is that he learned how to make his beliefs actionable, via precise and practical techniques. Lincoln was a skilled storyteller, and a great orator. He told jokes, he relied on sarcasm, and often made fun of himself. But behind the banter was a master storyteller, who carefully chose what to say and what to withhold. He knew his limitations and, as history came to prove, he knew how to prioritize. As the host of NPR's Morning Edition for almost two decades, Inskeep has mastered the art of bridging divides and building constructive debate in interviews; in Differ We Must, he brings his skills to bear on a prior master and in doing so forms a fresh and compelling narrative of Lincoln's life"--